Effect of shell thickness on heterostructure of CdSe/CdS core/shell nanocrystals - Le, Anh Thi; Man, Minh Tan; Nguyen, Minh Hoa (Hue University Journal of Science: Natural Science, 2022)
Core/shell hetero-nanostructures are promising materials for fabricating optoelectronic devices, photodetectors, bioimaging, and biosensing. The CdSe/CdS core/shell nanocrystals (NCs) were synthesized in a wet chemical reaction. The shell thickness was modified by varying reaction times. The structure and optical properties as a function of the CdS shell thickness were investigated. A systematic redshift of the first exciton absorption peaks and photoluminescent (PL) spectra occurred after coating with CdS confirmed the shell growth over the CdSe core. The PL’s intensity increased compared with that of bare NCs. The formation of high-quality NCs with uniform size distribution was shown in the transmission electron microscopy (TEM) image and confirmed by the narrow PL band and small FWHM.